Analisis Implementasi Kebijakan Tunjangan Profesi Guru di SD Negeri Sumbersari 1 Malang - Wasila, Nur Fatkhiya Warda (Universitas Negeri Malang, 2024)
Abstract The purpose of writing this research is to analyze the implementation of the teacher professional allowance policy at SDN Sumbersari 1 Malang City. This research applies a qualitative approach with a case study method. This research uses data sources in the form of primary and secondary data. Data collection techniques include interviews, observation and documentation. The results of this research are that the process of implementing the teacher professional allowance policy at SDN Sumbersari 1 Malang involves several stages involving various parties. The school together with the local education supervisor conducted a needs analysis to assess the extent to which the policy could provide benefits for teachers at the school. This step involves evaluating teacher performance, teaching experience, and educational qualifications as a basis for determining the amount of professional allowances.